A novel reversible colorimetric chemosensor for the detection of Cu2+ based on a water-soluble polymer containing rhodamine receptor pendants1. Issue 24 (15th March 2015) - Li, Guang; Tao, Farong; Wang, Hu; Wang, Liping; Zhang, Jiaojiao; Ge, Peipei; Liu, Lin; Tong, Yunhua; Sun, Su
<x xml:space="preserve">Abstract</x> A novel reversible colorimetric chemosensor based on water-soluble polymer toward Cu2+ ions in pure aqueous solution has been developed.